INFLUENCER MARKETING ON SOCIAL MEDIA: EXPLORING THE ROLE OF SOURCE CREDIBILITY IN GENERATING PARA SOCIAL RELATIONSHIPS AND PRODUCT INTEREST - Seerat Fatima; Usamah Iyyaz Billah (International Journal of Business Reflections, 2023)
The purpose of this research is to examine the relation of influencer credibility with product interest through the mediation of para-social relationships. Influencer credibility was measured through the constructs of expertise, attractiveness, trustworthiness, and similarity. By making a conceptual framework and then evaluating it, this research tries to fill the theoretical gaps about the study variables in a digital influencing context. A questionnaire was developed based on items from available literature about the study variables. The target respondents of the study were social media users from Pakistan who are also users of various brands. The data analysis was conducted using the Process “Macro by Hayes” model 4 in SPSS. Key findings show that the credibility of a source is important for building parasocial relationships and product interest. All the hypotheses were supported showing the immense importance of influences in brand Marketing in the current era. The underpinning theory of this study is the source credibility theory which is supported by our findings. The study also opens new avenues for future research including the application of the model in e-commerce and business-to-business sectors of the industry. The results of this research will also help brand managers and digital marketers design their promotional campaigns through the endorsement of online influencers.